Creativity and Aging - Mundell, Kathleen (Maine Policy Review, 2015)
Kathleen Mundell discusses the importance of creativity and creative engagement for older adults and their communities. She describes several projects sponsored by the Creative Aging Program of the Maine Arts Commission, which is one of 14 state arts agencies invited to participate in a national pilot program as part of the National Center for Creative Aging’s Engage Initiative.